2020
DOI: 10.34069/ai/2020.35.11.5
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Electronic Customer Relationship Management System Adoption In Telecommunication Companies

Abstract: Employee satisfaction is key to electronic–customer relationship management (E-CRM) systems in telecommunication companies. The purpose of this study is to investigate the direct and indirect effect of technological factors, individual factors, and organizational factors on employees' level of satisfaction. For this study, data was collected from 300 employees' workings in Malaysian telecommunication companies; and the data was analyzed using PLS-SEM. The findings revealed that technological, organizational, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The cognitive effort the system needs in navigating the network usability is the ease of usage (Al-Mamary et al, 2015; Grabarics et al, 2017;Howes et al, 2017;Kilsby et al, 2017). (Anaam et al, 2020;Anaam, Magableh, et al, 2021) indicated that to examine the consequences of an individual's personal impact on technology acceptance and improvement, is to confirm the significant favorable impacts of E-CRM on ease of use as a form of personal impact in technology acceptance (Olayah, Anaam, Yahya, et al, 2022). A significant difference among perceived utility and user satisfaction of use highlighted is fundamental to the relationship between perceived job satisfaction and performances.…”
Section: Ease Of Usementioning
confidence: 99%
“…The cognitive effort the system needs in navigating the network usability is the ease of usage (Al-Mamary et al, 2015; Grabarics et al, 2017;Howes et al, 2017;Kilsby et al, 2017). (Anaam et al, 2020;Anaam, Magableh, et al, 2021) indicated that to examine the consequences of an individual's personal impact on technology acceptance and improvement, is to confirm the significant favorable impacts of E-CRM on ease of use as a form of personal impact in technology acceptance (Olayah, Anaam, Yahya, et al, 2022). A significant difference among perceived utility and user satisfaction of use highlighted is fundamental to the relationship between perceived job satisfaction and performances.…”
Section: Ease Of Usementioning
confidence: 99%
“…The findings show that Fuzzy systems with decision trees at each node and correlations approaches outperformed Algorithmic segmentation and vector similarities techniques through a range of scenarios. Bayesian methods [29] Combining numerous components evaluations can enhance the recommendations. Collective intelligence [30] Recommending a method for recommending items to a prospective user.…”
Section: Techniques Main Findings Techniques/ Algorithmsmentioning
confidence: 99%
“…Though there were several guidelines on the adoption method of E-CRM, the unsuccessful ranks for E-CRM continue perniciously in height. Several types of research have shown that 60% of E-CRM efforts are observed as unproductive adoption in developed countries, while only 40% are observed as achievements [29], [30]. There has been no study on the recommendation system with E-CRM employing both the perceptual cycle model to evaluate differences in satisfaction with service quality.…”
Section: G Theoretical Gapmentioning
confidence: 99%
“…What one employee might consider a PCB may not be a breach for another employee. Individual differences can affect how strongly employees respond to breaches (Robinson & Morrison, 2000;Zhao et al, 2007;Anaam et al, 2020;. Therefore, the effects of individual variables must be examined.…”
Section: The Moderating Role Of Tenurementioning
confidence: 99%